2018
DOI: 10.1111/adb.12633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heroin on rat prosocial behavior

Abstract: Opioid use disorders are characterized in part by impairments in social functioning. Previous research indicates that laboratory rats, which are frequently used as animal models of addiction-related behaviors, are capable of prosocial behavior. For example, under normal conditions, when a 'free' rat is placed in the vicinity of rat trapped in a plastic restrainer, the rat will release or 'rescue' the other rat from confinement. The present study was conducted to determine the effects of heroin on prosocial beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…That drug supposedly blocked “affective processing”, so the authors concluded that affect (i.e., empathic concern) was necessary to motivate rescue behavior. Interestingly, a similar result was obtained with heroin [ 82 ]. At that point, the empathy-based explanation of rescue activities in rats was again attacked [ 83 , 84 ].…”
Section: Rescue Behavior In Other Taxasupporting
confidence: 78%
“…That drug supposedly blocked “affective processing”, so the authors concluded that affect (i.e., empathic concern) was necessary to motivate rescue behavior. Interestingly, a similar result was obtained with heroin [ 82 ]. At that point, the empathy-based explanation of rescue activities in rats was again attacked [ 83 , 84 ].…”
Section: Rescue Behavior In Other Taxasupporting
confidence: 78%
“…Approximately 17% of the rats tested by Ben-Ami Bartal et al [45] rescued within the first hour of their first trial. Moreover, none of the forty-six rats tested by Tomek et al [51] opened the restrainer door within the first two minutes of their first trial (Per. Comm.).…”
Section: Comparisons To Ratsmentioning
confidence: 99%
“…They claimed not only that the rats showed helping behaviour, but that it was motivated by a form of empathy [21]. In follow-up studies to Bartal and colleagues seminal paper, researchers have demonstrated the influence of social learning history, anxiolytics and opioids on the helping behaviour of rats [3739]. However, rigorous experimental control and detailed knowledge about influencing variables are needed to draw firm conclusions regarding the observations (i.e., empathic motivations and pro-social intentions).…”
Section: Introductionmentioning
confidence: 99%